Modification of YOLOv11 Architecture with Convolutional Block Attention Module Integration for Batik Besurek Motif Detection - Reksi Hendra Pratama; Ernawati; Widhia Oktoeberza KZ (Center for Research and Community Service, Institut Informatika Indonesia (IKADO) Surabaya, 2026)
Batik Besurek is a distinctive cultural heritage textile from Bengkulu, characterized by the combination of Arabic calligraphy, floral, and faunal motifs. However, public recognition of these motifs continues to decline, particularly among younger generations, creating an urgent need for digital preservation through modern computer vision techniques. This study aims to develop an enhanced object detection model for identifying Batik Besurek motifs by integrating the Convolutional Block Attention Module (CBAM) into the Neck (feature fusion layers) of the YOLOv11 architecture. A total of 3,876 images were collected from online repositories and field documentation in Bengkulu, followed by annotation and data augmentation using the Roboflow platform. Specifically, Mosaic augmentation combined with a close-mosaic strategy proved most significant in stabilizing the detection of dense and minority motifs. The research employs an experimental methodology by constructing two models, standard YOLOv11 as the baseline and YOLOv11+CBAM as the proposed model, trained under identical hyperparameter configurations. Model performance was evaluated using standard object detection metrics, namely precision, recall, mAP@50, and mAP@50–95. The experimental results demonstrate that the integration of CBAM significantly improves feature extraction capability, enabling the model to better capture dense, small, and visually complex batik motifs. The proposed model outperforms the baseline across all metrics, achieving a mAP@50 of 0.988, mAP@50-95 of 0.914, Recall of 0.971, and Precision of 0.959. These results indicate superior sensitivity and localization accuracy, particularly for minority motif classes, confirming that incorporating attention mechanisms into YOLOv11 provides a robust solution for the digital preservation of Besurek patterns.